Definition of quality of life in people with disabilities. - Kyrychenko, A. G. (Medicni Perspektivi, 2014)
In order to determine quality of life of people with disabilities according to age, gender and functional limitations using questionnaire SF-36 study was conducted. The study was conducted by examining questionnaire data and performed using the comparison of the data in the standard forms of primary documentation. It was revealed that in disabled caused by diseases of the nervous system a significant decrease of quality of life by the most scales of SF-36 questionnaire, was noted it is reliable, valid, and a highly convenient method of assessing physical and mental health of persons with disabilities and allows to control various components of life activity and has prognostic significance with respect to the effectiveness of rehabilitation, reintegration and resocialization.